Britain and Japan : Biographical Portraits, Vol. VI. - Cortazzi, Hugh (BRILL, 2007)
This sixth volume in the Britain and Japan series contains a total of thirty-three entries, thoughtfully and painstakingly compiled and edited by Hugh Cortazzi. The volume is divided up thematically and includes an Index of Biographical Portraits published to date by the Japan Society.